MODEL OF STRATIFIED LUBRICATION OF ELASTICALLY DEFORMED RADIAL BEARING - Sergey Vladimirovich Mitrofanov; Boris vgenyevich Kopotun (Advanced Engineering Research)
On the basis of the Navier-Stokes equations for the case of a ‘thin layer’, the continuity equation, Lame equations, and Darcy equation, considering the boundary conditions on the pin and bearing face at the layer interface, a method of generating an exact self-similar solution to the problem of calculating the hydrodynamic elastically deformed radial bearing working on a two-layer lubrication and having damping properties is provided. The problem solution is resulted in identifying the velocity and pressure field in the lubricating layer, and in obtaining the analytical expressions for the basic performance of the elastically deformed radial bearing. A numerical analysis of the obtained analytical expressions for the non-dimensional load-carrying capacity of the elastically deformed radial bearing with a porous layer on the pin surface is performed. The effect of the parameter values providing the bearing with an increased load-carrying capacity is assessed.